Swelling-induced telephone cord blisters in hydrogel films - Yuan, Bo; Harvey, Christopher M.; Shen, Ke; Thomson, Rachel; Critchlow, Gary; Rickerby, David S.; Yu, Suyuan; Wang, Simon (Elsevier, 2021)
Polymeric hydrogels can undergo dramatic shape and volumetric change when immersed into an appropriate solvent due to swelling or shrinking. Experimental studies have observed a variety of instability patterns in hydrogels. The telephone cord blister (TCB) with large deformability is one intriguing instability pattern but the assessment of its global morphology parameters, that is, the wavelength and transverse amplitude are still of inadequate appreciation. The present paper considers swelling-induced TCBs in a hydrogel-based film on a rigid substrate. Based on a previously developed theoretical framework for TCBs under small deformation, typically in a hard thin film, the theoretical derivations for the two global morphological parameters are furthermore developed for TCBs under large deformation in a soft thin film. Predictions for the morphology parameters of the developed theory agree very well with extensive experimental results. The critical mechanical conditions associated with the material-specific parameters such as the cross-linking density and swelling ratio are revealed. In addition, by reversing the calculation, the swelling-induced compressive stress in the un-delaminated film and the interfacial adhesion toughness are also accurately determined from measurements of the hydrogel TCBs. The present work provides an insight to design the microfluidics by controlling the morphology parameters with high precision.
Keywords: Telephone cord blister; Compressive stress; Adhesion toughness; Hydrogel; Swelling; Buckling